ChemInform Abstract: Catalytic Asymmetric Iodocyclization of N‐Tosyl Alkenamides Using Aminoiminophenoxy Copper Carboxylate: A Concise Synthesis of Chiral 8‐Oxa‐6‐azabicyclo[3.2.1]octanes. Issue 10 (February 2016) - Arai, Takayoshi; Watanabe, Ohji; Yabe, Shinnosuke; Yamanaka, Masahiro
Abstract: The novel iodocyclization of alkenamides affords O‐cyclized products with high enantioselectivities.